Compressive behaviour of basalt FRP and basalt-carbon hybrid frp laminates - Mengal, A.N. (Asian Research Publishing Network, 2016)
In this study the compressive strength of new basalt FRP and basalt-carbon hybrid FRP composite laminates were investigated experimentally. The main aim of this paper is to determine the influence of fiber orientation on compressive strength and to estimate the compressive strength of basalt FRP and basalt-carbon hybrid FRP composite laminates. The test specimens with varying orientations were prepared using hand lay-up technique. Compression test was performed according to ASTM test standard D6641 procedure A (untabbed specimens). The different composite laminates included in this study were pure basalt, pure carbon and six hybrid composite laminates. From the experimental analysis the fibre orientation was found to influence the compressive strength of basalt-carbon hybrid composite laminates. All the hybrid composite laminates showed a positive hybridization effect. The basalt-carbon/epoxy hybrid composite C2 with angle ply layup of 02C/+45B/0B S was found to be the optimum lay-up with highest compressive strength among all the other laminates. Â©2006-2016 Asian Research Publishing Network (ARPN).